Competitividade internacional das cidades olímpicas: o caso do Rio de Janeiro - Mendes, Marcos Vinícius Isaias (2017)
Evaluate the international competitiveness of Rio de Janeiro in the context of Rio 2016, under the point of view of attracting foreign investments. The theoretical framework evaluated allowed us to identify two relevant streams of analysis for this purpose: the global city theory and the new modalities of public management. Based on them, an international competitiveness framework for the city was developed, covering 4 research questions and 13 analysis categories. The methodology employed involved five semi-structured interviews with actors from Agência Rio-Negócios (Rio-Business Agency), the International Relations Coordination (CRI), the Rio Operations Center (COR) and the Special Secretariat for Concessions and Public-Private Partnerships (SECPAR), all linked to the city hall. In addition, the participant-observation method was used to evaluate the different narratives about smart city, in events occurred in Rio de Janeiro between 2015 and 2016. Among the results of the study, it was verified that the activism and the international competitiveness of the city grew considerably over the period from 2009 to 2016. Evidence of this was a 31.5% increase in the number of twinning agreements or partnerships with international cities and a 66.7% increase in the participation in international city networks. Moreover, evidences were identified of new public management, new public governance and new public service in the city management, in particular: frequent use of Public-Private Partnerships (PPP), adoption of meritocracy systems, management by results, use of information technologies and e-government. Finally, of the 13 categories created, 12 pointed to the increase in the international competitiveness of the city in the context of preparation to the Rio 2016 Olympics.